Interferon regulatory factor 6 correlates with the progression of non-small cell lung cancer and can be regulated by miR-320. (6th March 2021) - Liu, Yunpeng; Shao, Guoguang; Yang, Zhiguang; Lin, Xingyu; Liu, Xing; Qian, Benxin; Liu, Zihao
Abstract: Objectives: The expression of interferon regulatory factor 6 (IRF6) has been reported in several cancer types, but its roles underlying the progression of lung cancer have not been detailedly investigated. Methods: The pairs of lung cancer tissues and para-carcinoma tissues and The Cancer Genome Atlas database were collected to detect IRF6 expression. Cell counting kit-8, transwell and terminal-deoxynucleoitidyl transferase-mediated nick end labelling assays were used to evaluate cell proliferation, migration and apoptosis. Key findings: A significant up-regulation of IRF6 in both lung adenocarcinoma and lung squamous cell carcinoma tissues compared with normal non-tumor tissues. Subsequently, Immunostaining also revealed that canceration of lung tissues predisposed to evoke IRF6 expression. In vitro experiments revealed the antitumour effects, including growth and migration inhibition, of IRF6 siRNA transfection. Considering miR-320 as an endogenous inhibitor to IRF6, miR-320 mimics transfection led to the inhibition of proliferation and migration of lung cancer cells. However, overexpressed IRF6 neutralized the antineoplastic activities of miR-320 in lung cancer cells. Conclusions: The miR-320/IRF6 signalling axis was implicated in pulmonary canceration. miR-320 as an endogenous inhibitor of IRF6 provided a novel therapeutic strategy for the treatment of lung cancer.